Electoral Violence and Democratic Consolidation in Nigeria - Ameh-Ogigo, James Arome (Kashere Journal of Politics and International Relations, 2024)
Electoral violence remains a significant challenge to democratic consolidation in Nigeria. The country’s transition to democratic governance has been marred by frequent violent conflicts during election periods, undermining the legitimacy of electoral outcomes and eroding public trust in democratic institutions. This paper examines the root causes of electoral violence in Nigeria, including ethnic tensions, economic inequality, and weak state institutions. It further explores the impact of such violence on democratic consolidation, focusing on how it disrupts political stability, hinders voter participation, and encourages authoritarian tendencies. The study was anchored on the basic proposition of frustration-aggression theory originally proposed by Dollard, Doob, Miller, Mowrer, and Sears (1939), believes that the primary source of human capacity for crisis or violence is the aggression mechanisms. The anger induced by frustration is a motivating force that disposes people to aggression irrespective of its instrumentalities. In conclusion, the paper argues that addressing electoral violence through reforms in the electoral processes, strengthening rule of law, and promoting inclusive political participation are essential steps toward sustainable democratic consolidation in Nigeria.